Effect of ischemia on intestinal permeability of lipopolysaccharides - Drewe, Jürgen; Beglinger, Christoph; Fricker, Gert (European journal of clinical investigation, 2001)
The enteral absorption of endotoxin (lipopolysaccharide, LPS) was studied in vitro and in vivo. The absorption of fluorescence (FITC) labelled LPS was investigated by uptake studies with rabbit jejunal brush-border membrane vesicles (BBMV), the human intestinal cell line Caco-2 and in rats. FITC-LPS from Salmonella typhimurium was taken up into BBMV in a dose-dependent manner. Uptake was neither pH- nor Na+-dependent, nor could it be inhibited by unlabelled LPS. 74·5% of vesicle-associated fluorescence was due to adhesion to the vesicular membranes, 25·5% was taken up into an osmotically-sensitive space. Transport of LPS across Caco-2 cell monolayers was dose-dependent. The permeation rate increased significantly under ischemic conditions, i.e. when the cells were incubated under oxygen-depleted conditions. However, no significant differences in transepithelial electrical resistances were observed between oxygen depleted and control cells. The release of lactate dehydrogenase was only marginally different from control cells, indicating cell integrity. In situ, after gut ischemia, a significantly increased uptake of fluorescent LPS was observed by fluorescence laser scanning microscopy. Conclusion LPS is taken up by the intestinal mucosa, predominantly by passive transcellular diffusion. Under ischemic conditions, the permeability of LPS is increased mainly by an enhanced paracellular permeability and epithelial destruction. The findings partly explain the clinically observed development of multiorgan system failure after temporary malperfusion of the gut during major vascular surgery or thromboembolism.